The Influence of Teacher Certification on the Pedagogical Competence of Early Childhood Education Teachers in Karangawen District, Demak Regency - Diana; Dinina Dzawin Najah (BELIA Early Childhood Education Papers, 2025)
This study aims to determine the effect of teacher certification on teacher pedagogical competence (PAUD) in Karangawen District, Demak Regency. Teacher certification is expected to improve pedagogical competence, which includes understanding and implementing effective teaching methods for early childhood. This study uses a quantitative approach with a survey method with the population of this study being PAUD teachers who have been certified in Karangawen District, Demak Regency. The samples were taken from 30 PAUD teachers who had been certified in Karangawen District, Demak Regency, with a systematic nonprobability sampling. The data analysis technique used a simple linear regression test with a hypothesis test using the t-test, the coefficient of determination (R-Square). The results of the reliability test were 0.745. The data analysis used was the normality test using the Kolmogorov-Smirnov method with a significance value of 0.200> 0.05. Based on the simple linear regression test, it shows a significance value of 0.000, which is smaller than the probability value of 0.05. Thus, it can be concluded that hypothesis Ha stating that there is an influence of teacher certification on the pedagogical competence of PAUD teachers is accepted, and hypothesis Ho is rejected. The results of the R Square value of 0.998 or 99.8%, show that teacher certification has a significant effect on the pedagogical competence of PAUD teachers